Ocular Morbidity at High Altitude in Nepal - Shrestha, Sabina; Manoranjan, Aparajita; Shresthatha, Sushan Man (Medical Journal of Shree Birendra Hospital, 2017)
Introduction: Certain changes occur in high altitude which can be organic, motor or functional. This study was conducted to find out ocular morbidity at high altitude in Nepal. Methods: A cross sectional study was conducted at four different places at altitudes of 2710 m (Jomsom), 2900 m (Kagbeni), 3500 m (Jharkot) and 3800 m (Muktinath) of Mustangdistrict of Nepal using convenient sampling method. A total of 222 subjects (444 eyes) were included. They were examined for vascular engorgement and tortuosity, arteriovenous ratio changes, retinal hemorrhages, cataract, pterygium, color vision and intraocular pressure. The motor changes like esodeviation and exodeviation were studied. Results: Of the total 222 participants, 164 (77.5%) were more than 40 years of age and 58 (22.5%) were less than 40 years. The male to female ratio was 1:1.1. The duration of stay at high altitude was >10 years in 96.6%, >15 years 88.3% and >20 years 83.8%. The prevalence of cataract was 19.8% and pseudophakia 17.1%. Other organic changes like venous engorgement, arterio-venous ratio changes and venous tortuosity was also found at high altitude. There was no significant change in intraocular pressure at high altitude. Esodeviation was present in 14%. The prevalence of pterygium was present in 39.6%. Similarly, the prevalence of red green color vision deficiency was 45.1%. Conclusion: Cataract, pterygium, red green color vision deficiency, esodeviation, venous engorgement and venous tortuosity were found to be prevalent at high altitude of Nepal.